2019
DOI: 10.1155/2019/3609642
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Weight Loss, and Not Weight Loss Rate, Is Associated with Better Improvements in Metabolic Health

Abstract: Objective. To determine if the rate of weight loss (WL) is associated with metabolic changes independent of the absolute WL. Methods. WL and health changes were assessed in 11,281 patients attending a publicly funded clinical weight management program over a treatment period of 12.7 months. Early weight loss rate (WLR) in the first 3–6 months and overall WLR were categorized as Fast WLR (≥1 kg/wk), Recommended WLR (0.5 to 0.9 kg/wk), or Slow WLR (<0.5 kg/wk). Results. On average, patients attained a 6.6 ± 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Consequences associated with rapid body mass loss might include the worsening of specific health biomarkers (182) while the improvement of others (154,195) or detrimental body composition changes in athletes (70). However, because most of these studies are performed in obese or overweight individuals, it could be argued whether any of the benefits observed are because of the body mass loss rate or the absolute body mass loss per se (113). In a recent comprehensive systematic review on this topic (116), it was concluded that gradual rates of weight loss were associated with greater losses in FM and body fat percentage as well as an enhanced maintenance of REE.…”
Section: Rate Of Body Mass Lossmentioning
confidence: 99%
“…Consequences associated with rapid body mass loss might include the worsening of specific health biomarkers (182) while the improvement of others (154,195) or detrimental body composition changes in athletes (70). However, because most of these studies are performed in obese or overweight individuals, it could be argued whether any of the benefits observed are because of the body mass loss rate or the absolute body mass loss per se (113). In a recent comprehensive systematic review on this topic (116), it was concluded that gradual rates of weight loss were associated with greater losses in FM and body fat percentage as well as an enhanced maintenance of REE.…”
Section: Rate Of Body Mass Lossmentioning
confidence: 99%